2015
DOI: 10.15361/1984-5529.2015v43n4p348-352
|View full text |Cite
|
Sign up to set email alerts
|

'Imperial' melon plant seedlings initial development in function of boron doses applied in the seed

Abstract: The melon has little boron deficiency tolerance and supply as seed treatment can meet the need of the plant and improve its development especially in the seedling stage. The objective of this study was to evaluate the initial development of muskmelon seedlings 'Imperial' on the basis of boron application in seeds. The experiment was conducted under greenhouse conditions (50% brightness) in Bom Jesus-PI in the period April-May 2011. It was adopted a randomized block design, with treatments: 0.0; 4.24; 8.50; 17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Likewise, Pessoa et al (2000) observed that maize seeds treated with B doses equal to or greater than 0.2 g kg -1 had a decrease in leaf and root dry masses. When applying B to melon seeds, Albano et al (2015) found that an increase in B doses increased shoot dry mass up to 12.3 g kg -1 seed, followed by a small decrease with increasing B doses. The same authors observed that root dry mass increased at a dose of 10.5 g kg -1 B, and above that, it reduced.…”
Section: Tablementioning
confidence: 99%
“…Likewise, Pessoa et al (2000) observed that maize seeds treated with B doses equal to or greater than 0.2 g kg -1 had a decrease in leaf and root dry masses. When applying B to melon seeds, Albano et al (2015) found that an increase in B doses increased shoot dry mass up to 12.3 g kg -1 seed, followed by a small decrease with increasing B doses. The same authors observed that root dry mass increased at a dose of 10.5 g kg -1 B, and above that, it reduced.…”
Section: Tablementioning
confidence: 99%